Pengaruh Kepemimpinan Spiritual dan Budaya Sekolah Terhadap Kinerja Guru pada Ponpes Modern IGM Al Ihsaniyah - Dea, Ara; Afriyani, Fauziah; Emilda (Jurnal EMT KITA, 2025)
-The purpose of this study was to the effect of spiritual leadership and school culture on teacher performance at IGM Al ihsaniyah modern boarding school. The population and sample in this study were 51 teachers at the IGM Al Ihsaniyah Modern Islamic Boarding School. The sampling technique in this research used a saturated sampling technique. Data was collected by distributing questionnaires and then analyzed using Statistical Product and Service Solution (SPSS) version 22. The results of this research show that there is an influence of spiritual leadership and organizational culture on the performance of teachers at the IGM Al Ihsaniyah Modern Islamic Boarding School. Based on the results of the explanation of the data obtained, (1) The multiple linear regression equation obtained the final equation, namely Y = 14.307 + 0.413X1 + 0.741X2 + e. (2) spiritual leadership has no effect and is not significant on teacher performance as seen from the results of the t test with a value of t calculated > t table or 1.753 < 2.00958 and significant 0.086 > 0.05, school culture has an effect and is significant on teacher performance as seen from the results of the t test with the value t count > t table 3.194 > 2.00958 and significant 0.002 < 0.05. (3) The results of the F test show that spiritual leadership and school culture have a significant and influential effect on teacher performance. F count > F table is 31,933 > 3.19 with a significant value of 0.00 < 0.05. (4) Based on the results of the coefficient of determination test (R2), spiritual leadership and school culture are able to explain teacher performance variables by 0.554 or 55.4%.